History of Vegetation and Agriculture: At Hassing Huse Mose, Thy, Northwest Denmark, since the Ice Age - Th., Svend (Journal of Danish Archaeology, 1993)
History of Vegetation and Agriculture: At Hassing Huse Mose, Thy, Northwest Denmark, since the Ice Age